Testosterone Levels and Sexual Function Disorders in Depressive Female Patients: Effects of Antidepressant Treatment. (1st February 2014) - Kumsar, Şükrü; Kumsar, Neslihan Akkişi; Sağlam, Hasan Salih; Köse, Osman; Budak, Salih; Adsan, Öztuğ
Abstract: Introduction: Women suffer from depression more frequently than men, which indicates that sex hormones might be involved in the etiology of this disease. Aims: The purpose of this study was to assess the relationship between testosterone and depression pathophysiology in depressive women along with sexual function. We also investigated whether antidepressant treatment causes any change in levels of this hormone or in sexual function. Methods: Premenopausal female patients aged 25–46 years (n = 52) with diagnosed major depression were included in this study as the patient group, and 25‐ to 46‐year‐old premenopausal women without depression (n = 30) were included as the control group. Main Outcome Measures: Serum testosterone and sex hormone‐binding globulin (SHBG) levels were measured twice, before and after the antidepressant treatment. Bioavailable testosterone (cBT) levels were calculated using the assay results for total testosterone (TT), SHBG, and albumin according to the formulas of Vermeulen et al. Depression severity was measured using the 17‐item Hamilton Depression Rating Scale, and sexual function was evaluated with the Arizona Sexual Experience Scale. Results: The mean TT and cBT levels significantly increased in the patient group after the antidepressant treatment ( P < 0.001). Pre‐treatment TT and cBT levels were significantly lower in the patient group than in the control group ( P < 0.001). Similar results were obtained for post‐treatment serum TT and cBT levels in the patient and control groups ( P > 0.05). There were no significant differences among the groups in terms of SHBG level. Conclusion: The low testosterone levels in depressed women compared with women in the control group and the elevated levels post‐pharmacotherapy suggest that testosterone may be involved in depression.